Her Favorite Husband - Logan, Leandra (Toronto Harlequin Books, 1994)
A DIFFERENT MAN EVERY NIGHT OF THE WEEK Monday's husband liked starch in his socks, while Wednesday's man was so laid-back. Madeline Clancy had a hard time getting him to remember his girlfriend's birthday! It was all part of the services of JUST LIKE A Wife. But Madeline's favorite guy was Friday. She'd never met him, the man was always on business, but his faxes were to die for. As was his downtown apartment building-a perfect place to meet eligible, successful men. So, on Fridays, Maddy moved in. And ran into Trey Turner-bachelor number five. First he tried to pick her up. Then he fired her! And then he begged her to pretend to be his wife. How could a girl say no?
Keywords: American Fiction